2017
DOI: 10.1111/ppa.12715
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in sdh genes in field isolates of Zymoseptoria tritici and impact on the sensitivity to various succinate dehydrogenase inhibitors

Abstract: Zymoseptoria tritici is the causal agent of septoria tritici blotch (STB), a foliar wheat disease important worldwide. Succinate dehydrogenase inhibitors (SDHIs) have been used in cereals for effective control of STB for several years, but resistance towards SDHIs has been reported in several phytopathogenic fungi. Resistance mechanisms are target-site mutations in the genes coding for subunits B, C and D of the succinate dehydrogenase (SDH) enzyme. Previous monitoring data in Europe indicated the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
114
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 88 publications
(119 citation statements)
references
References 15 publications
4
114
1
Order By: Relevance
“…The detection of strains highly resistant to fluopyram, and in particular isofetamid, in multiple locations as early as 2003 (Table ), before the widespread introduction of a newer generation of SDHIs into the cereal market in 2010, indicates pre‐existing non‐target site resistance. We have also seen that European Z. tritici populations have developed acquired resistance only through a range of different Sdh target‐site mutations since 2012 . In addition, strains with altered efflux pump activity, including MgMFS1 ‐overexpressing strains have recently spread in Europe as a response to selection by QoI, azole and SDHI fungicides.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The detection of strains highly resistant to fluopyram, and in particular isofetamid, in multiple locations as early as 2003 (Table ), before the widespread introduction of a newer generation of SDHIs into the cereal market in 2010, indicates pre‐existing non‐target site resistance. We have also seen that European Z. tritici populations have developed acquired resistance only through a range of different Sdh target‐site mutations since 2012 . In addition, strains with altered efflux pump activity, including MgMFS1 ‐overexpressing strains have recently spread in Europe as a response to selection by QoI, azole and SDHI fungicides.…”
Section: Discussionmentioning
confidence: 99%
“…For cross‐resistance studies, reference strain IPO323‐derived laboratory mutants and field isolates, for which the Sdh genotypes had been analysed previously,, , were tested. For additional field population monitoring studies, sampling and isolation of Z. tritici strains from infected wheat leaves were performed as described previously .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of QoIs, it has been reported that the orthologous amino acid mutations result in similar resistance profiles across different organisms with respect to the strength of resistance; the G143A mutation causes very high level of resistance (the resistance factor RF, [EC 50 of the resistant mutant]/[EC 50 of the wild type], is always greater than 100) to all commercial QoIs in any known cases of more than 20 pathogen species . However, recently some cases of different resistance profiles within the orthologous mutations of different pathogen species were reported in cases of resistance against succinate dehydrogenase inhibitor (SDHI), another important agricultural fungicide class . Considering the unique behavior of metyltetraprole in the G143A mutants of Z. tritici as well as in the F129L mutants of P. teres , its consistency in orthologous mutations in different species should be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, only three classes of fungicides, DMI (sterol C14 demethylation inhibitor in ergosterol biosynthesis), QoI (Qo site of complex III inhibitor in the respiratory chain), and SDHI (succinate dehydrogenase inhibitor in the respiratory chain), have accounted for approximately 60% of the global fungicide market because of their high efficacy and the broad spectrum of these three chemical classes. Frequent usage of these three classes of fungicides has led to the development of resistance in crop pathogens, such as Zymoseptoria tritici , Erysiphe necator , Podosphaera xanthii , Microdochium spp., and Cercospora beticola . As a result, agrochemical research and development seek new chemical classes of fungicides to respond to the needs of crop growers .…”
Section: Introductionmentioning
confidence: 99%